An update on the genetics of dementia with Lewy bodies. (October 2017) - Vergouw, Leonie J.M.; van Steenoven, Inger; van de Berg, Wilma D.J.; Teunissen, Charlotte E.; van Swieten, John C.; Bonifati, Vincenzo; Lemstra, Afina W.; de Jong, Frank Jan
Abstract: The genetic architecture of dementia with Lewy bodies (DLB) is increasingly taking shape. Initially, genetic research focused mainly on linkage and candidate gene studies in small series of DLB patients. More recently, association and exome sequencing studies in larger groups have been conducted, and have shown that several variants in GBA and the APOE ε4 allele are important genetic risk factors for DLB. However, genetic research in DLB is still in its infancy. So far, many genetic studies have been biased and performed in clinically and pathologically heterogeneous populations. Therefore, it is likely that multiple DLB-specific genetic determinants still have to be identified. To further our understanding of the role of genetics in DLB, future genetic studies should be unbiased and performed in large series of DLB patients, ideally with both a clinical diagnosis and pathological confirmation. The combination of genomic techniques with other research modalities, such as proteomic research, is a promising approach to identify novel genetic determinants. More knowledge about the genetics of DLB will increase our understanding of the pathophysiology of the disease and its relation with Parkinson's Disease and Alzheimer's Disease, and may eventually lead to the development of disease modifying treatments. Highlights: An up-to-date review of the genetics of dementia with Lewy bodies is provided. To date, rare variants in GBA and the APOE ε4 allele are the strongest risk factors. Other genetic determinants are increasingly being identified. Overlap with Parkinson's and Alzheimer's disease, genetic differences also present. Large, unbiased research is necessary to find new genetic determinants.